The Readiness of Disadvantaged Regions in Implementing E-Government in Indonesia: Case Study in East Seram Regency - Hasri Arey; Suripto Suripto; Rian D. Hapsari; Muhammad Firyal Akbar (Institut Pemerintahan Dalam Negeri, 2020)
The East Seram Regency is a disadvantaged region in Indonesia with many sub-districts that do not have access to internet and electricity. The remaining options for sub-districts was hindered because it is limited by wilderness and free oceans and the APBD (Regional Revenue and Expenditure Budget) in this regency is also limited. Although, the implementation of e-Government by the Regent are willing to follow the mandate of Presidential Regulation No. 95 of 2018 concerning Electronic-Based Government Systems (SPBE). The purpose of this study was to analyze and determine the readiness of the East Seram Regency in implementing the e-government system in Indonesia. This study used a mixture of qualitative and quantitative methods and data collection technique was also carried out by using a questionnaire for 76 respondents, in-depth interviews for 7 informants, and documentation. The result showed the quality of public human resources and civil servants in the field of communication and the informatics are low. Also, the ICT infrastructure such as internet, servers, networks, and computer equipment are inadequate. The East Seram Regency is a disadvantaged region that prioritizes physical development infrastructure rather than allocating a high budget for the information technology tools. Therefore, it is concluded that the East Seram Regency as one of the disadvantaged region in Indonesia whose Local Government is 'Not Ready' to implement an e-government system as mandated by Presidential Regulation No. 95 of 2018.